2002
DOI: 10.1146/annurev.ento.47.091201.145220
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and Behavior of First Instar Larval Lepidoptera

Abstract: Neonate Lepidoptera are confronted with the daunting task of establishing themselves on a food plant. The factors relevant to this process need to be considered at spatial and temporal scales relevant to the larva and not the investigator. Neonates have to cope with an array of plant surface characters as well as internal characters once the integument is ruptured. These characters, as well as microclimatic conditions, vary within and between plant modules and interact with larval feeding requirements, strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
529
4
26

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 468 publications
(580 citation statements)
references
References 203 publications
10
529
4
26
Order By: Relevance
“…The greater delay in feeding onset observed for species with non-glandular trichomes is likely to be of particular importance for herbivore species like M. sexta , where the neonates are colorless and depend on ingested plant material to camouflage their bodies and reduce the risk of predation[11]. As demonstrated in previous studies [7,16], the mode of action of glandular trichomes differs from that of non-glandular trichomes as damage to glandular trichomes activates JA (Jasmonic acid) mediated defense gene expression and often contain toxins, resins, or signaling molecules rather than causing physical damage to caterpillars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater delay in feeding onset observed for species with non-glandular trichomes is likely to be of particular importance for herbivore species like M. sexta , where the neonates are colorless and depend on ingested plant material to camouflage their bodies and reduce the risk of predation[11]. As demonstrated in previous studies [7,16], the mode of action of glandular trichomes differs from that of non-glandular trichomes as damage to glandular trichomes activates JA (Jasmonic acid) mediated defense gene expression and often contain toxins, resins, or signaling molecules rather than causing physical damage to caterpillars.…”
Section: Discussionmentioning
confidence: 99%
“…In the same system, we also demonstrated that non-glandular stellate trichomes cause physical injury to caterpillars and impede the ability of early instar caterpillars to locate the epidermis and commence feeding [3]. For neonate caterpillars of species like M. sexta , any delay in initiating feeding could potentially prove fatal due to increased risk of desiccation, starvation, and/or predation [11]. Later instars are thought to be less sensitive to leaf defenses and leaf nutritional quality [12], and we have observed that late-instar caterpillars tend to ingest trichomes along with leaf tissues while feeding.…”
Section: Introductionmentioning
confidence: 99%
“…Although adults are the primary life stage for dispersal of most lepidopterans, caterpillars of some species disperse from the original oviposition site and search for new host plants by ballooning (as neonates; Zalucki et al, 2002) or crawling. These larvae forage when suitable food sources are exhausted (Singer and Stireman, 2001), thus avoiding natural enemies (Bernays, 1997;Singer and Stireman, 2003), reducing competitive interactions (Kakimoto et al, 2003), limiting exposure to toxins or balancing nutrients (Singer and Stireman, 2001;Singer et al, 2002), or compensating for suboptimal oviposition choices by females (Beredegué et al, 1992;Roitberg and Mangel, 1993;Doak, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Together with their lipophilic exudates (flavonoid aglycones, waxes, terpenes, lipids), trichomes may protect leaves against extensive light, UV-B radiation, and desiccation (Ehleringer, 1982;Karabourniotis et al, 1993;Cockell and Knowland, 1999;Tattini et al, 2000;Juma et al, 2001), or they may form the first line of defense against herbivores by entrapping, deterring, or poisoning (Harborne, 1991;Wagner, 1991;Hare, 2002;Zalucki et al, 2002). For Solanaceae, in particular, trichome exudates are responsible for the mortality of neonate larvae; the removal of exudates using an ethanol solution increase larval survival (Gurr and McGrath, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the removal of exudates from the leaf surface increases the consumption rates of neonates (van Dam and Hare, 1998) and their mobility on the leaf surface, shortens the duration of larval development, and even increases pupal weight (Malakar and Tingey, 2000). In general, the highest mortality of lepidopteran larvae occurs during the first instar (Zalucki et al, 2002); such an effect in the first stages of larval development is the most beneficial, since it can dramatically reduce future biomass losses of the plant (Karban and Baldwin, 1997).…”
Section: Introductionmentioning
confidence: 99%